Kajian Tafsir Lisan tentang Kata Shift Pemuda "Hijrah" Menurut Ustadz Teuku Hanan Attaki di Instagram - Bunga Surawijaya Ningsih; Iezzatul Hasanah; M. Devan Ainun Na'im (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2022)
The occurrence of hijrah at the time of Prophet Muhammad is an event that cannot be forgotten in the hearts and hearts of all Muslims. Because this incident has a very high value in the history of the Islamic world. There are also many things that can be used as lessons. This study examines oral interpretation in the media on Instagram with a study on Ustadz Teuku Hanan Attaki (UHA). The main research question is how is UHA's verbal explanation of the word youth hijrah in the Qur'an and also what is the significance of UHA's oral interpretation of the word shift of youth hijrah in the Qur'an on Instagram. This approach uses a descriptive qualitative approach. The results of this study show that UHA in the interpretation of hijrah is to interpret QS. al-Muzzammil (74):10. In some commentaries, in general hijrah means an order to leave something because of displeasure, the command in this verse is accompanied by the sentence hijran jamilan, which means "in a good way" forbidden to work that is lawful, such as avoiding usury. In addition, UHA's oral interpretation of hijrah has a significance that is not in the written interpretation. It means that the oral interpretation of UHA' Hijrah is more acceptable to the audience because the interpretation is clearer at the moment.